Cystic Duct Anomalies Encountered During Laparoscopic Cholecystectomy (Medical Forum Monthly, 2024)
Objective: To determine frequency of cystic duct anomalies and its common types in patients during laparoscopic cholecystectomy.Study design: Descriptive / cross sectional study.Place and duration of study: This study was conducted at Liaquat University of Medical and Health Sciences, Jamshoro and in Rajputana Hospital, Hyderabad from July 2014 to December 2014. Materials and Methods: After all relevant investigations, patient with diagnosis of cholelithiasis was submitted for laparoscopic cholecystectomy. Final outcome of cases operated in terms of cystic duct (C.D) anomalies were entered on proforma provided to all operating surgeons having >5 years of experience.Results: A total of 301 patients were included in this study. The mean age of the patients was 40.58±16.82 years (range is 31-60 years) . Most of the patients were lie < 46 years 175(58.1%)only. Out of 301 numbers of cases 116(38.6%) patients were male and 185(61.4%) were females. Cystic duct anomalies were noted in 38 (12.6%) cases only. In the present study the most common and higher incidence rate of anomalies like Spiral cystic duct were observed. Statistically the Incidence was found to be higher than in the previous studies.Conclusion: In this study the most common & higher incidence rate of anomalies like Spiral cystic duct were observed. Statistically the Incidence was found to be higher previous studies. Identification and careful dissection especially with anomalies prevent the damage to biliary tree during laparoscopic cholecytectomy.